Urban Wastewater Utilization for Economic Activities in Dodoma Urban District, Tanzania - Sarah F. Mamboya; Albino J. Tenge; Zacharia S. Masanyiwa (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
In the semi-arid areas of Tanzania that experience frequent periods of drought, wastewater is a critical resource for landed and landless households. This wastewater, which is generated daily by a rapidly growing population, and which flows into the ground, supports a variety of livelihood activities that require water. This study was conducted among 215 randomly and purposively sampled respondents to assess the use of wastewater for economic activities for improving livelihood in Dodoma Municipality which is one semi-arid areas in Tanzania. Specifically, the study intended to (i) identify the economic activities practised, (ii) determine the main economic activities that utilize wastewater and, (iii) find out the extent of wastewater utilization for economic activities in the study area. Primary data were collected through a survey among wastewater users and semi-structured interviews with key informants. Secondary data were collected through documentary review of different documents obtained from the relevant offices and officials. Descriptive statistics including cross tabulation and frequency distributions were analysed. The findings show that the major economic activities that utilize wastewater are farming (48%), livestock keeping (41%), brick- making (32%) and fishing (9%). The majority of respondents used wastewater resource for gardening, mainly tomatoes (26 %), followed by green vegetables (18%), okra (18%) and cowpeas (17%). With regard to livestock keeping, the majority of respondents used wastewater for rearing cattle (42%), goats (32%) and pigs (10%). Despite the existing economic activities that utilize wastewater, wastewater is generally underutilized in the study area. Therefore, policy makers and other stakeholders should ensure full utilization of wastewater potentials including, construction of livestock watering areas, fishing ponds, dips and irrigation structures.